100k views
1 vote
Solve the equation 3(2x-3) = 6
a) x = 2.5
b) x = 10.5
c) x = 12
d) x = 2.5

2 Answers

2 votes

Answer: x = 2.5

Step-by-step explanation: To solve this equation, we start by distributing the 3 through the parenthses on the left side.

So we have 3(2x) which is 6x and 3(-3) which is -9.

So our equation now reads 6x - 9 = 6.

Solving from here, we need to isolate the term containing x which is 6x.

Since 9 is being subtracted from 6x, we add

9 to both sides of the equation to isolate the 6x.

On the left, the -9 and +9 cancel out and on the right, 6 + 9 is 15.

So we have 6x = 15.

Now we can finish things off by just

dividing both sides of the equation by 6.

On the left the 3's cancel and on the right, 15 divide by 6 is 2.5.

So x = 2.5.

User Morten Bork
by
6.3k points
3 votes

Answer:

Option A & D

Explanation:

=> 3(2x-3) = 6

=> 6x-9 = 6

=> 6x = 6+9

=> 6x = 15

Dividing both sides by 6

=> x = 2.5

User Dmondark
by
6.8k points